Enterostomy closure site hernias: a clinical and ultrasonographic evaluation - (:unkn) unknown (SPRINGER, 2008)
Background Parastomal hernia with a reported incidence of up to 50% is a major problem after ostomy formation. Hernias at the closure site may be a problem after the closure of the enterostomy. In this study, in addition to physical examination, we used ultrasonography (USG) in order to find the true incidence of ostomy closure site and laparotomy incisional hernias. Methods We examined patients with closed enterostomy sites by both physical examination and USG for the detection of hernias. Risk factors for hernia formation, such as age, gender, body mass index (BMI), ostomy type, and surgical site infections, were determined. Results The evaluation of 31 patients with ostomies resulted in a 32% incidence of closed ostomy site hernias when patient medical history, physical examination, and ultrasonographic examination were used together. With physical examination and USG, incisional hernias at the laparotomy incision were found in 58% of cases. USG was able to detect hernias which were not clinically evident at the ostomy closure site and the laparotomy wound. BMI, age, gender, ostomy type, and surgical site infection did not have a significant effect on hernia formation. Conclusion Ostomy closure site and laparotomy incisional hernias are important clinical problems with a high incidence after ostomies are closed. Closure of the enterostomy site should be regarded as a hernia repair rather than a simple fascial closure. USG is a valuable clinical tool in combination with physical examination for the detection of minor defects.
Keywords: Ostomy closure site hernia; Incisional hernia; Ultrasonography; Ostomy; Enterostomy; LOOP ILEOSTOMY CLOSURE; PARASTOMAL HERNIA; INCISIONAL HERNIA; COLOSTOMY CLOSURE; GROWTH-FACTOR; COMPLICATIONS; MESH; REPAIR; PREVENTION